Prevalence of newly diagnosed essential hypertension within one year postpartum: a systematic review and meta-analysisAJOG Global Reports at a Glance - Jennifer D. Kaminker; Alexandra MacMaster; Jessica Pudwell; Kira King; Graeme N. Smith (AJOG Global Reports, 2025)
Objective: Pregnancy induces a state of cardiovascular stress and can lead to long-lasting effects irrespective of complications in pregnancy. However, the magnitude of these effects needs to be clarified. This study seeks to determine the prevalence of newly diagnosed essential hypertension within one year postpartum among the obstetric population who experienced uncomplicated pregnancies. Data sources: A comprehensive search of the databases MEDLINE, Cochrane Central Register of Controlled Clinical Trials, EMBASE, Web of Science, and CINAHL was conducted for studies published up to March 2023. Study eligibility criteria: Studies that assessed healthy individuals between 12 weeks and one year postpartum with newly diagnosed essential hypertension (≥140/90) and without pregnancy complications were included. Case studies, systematic reviews, and meta-analyses were excluded, along with studies involving pregnant patients who were either less than three months or more than one year postpartum, those with pre-existing hypertension or pregnancy complications, or those with pre-existing medical conditions. Study appraisal and synthesis methods: Meta-analyses using random-effects models calculated pooled prevalence estimates and examined mean arterial pressure, systolic blood pressure, and diastolic blood pressure. Subgroup analyses considered the timing of blood pressure assessment, geographical location, and the presence of interventions. Results: In eight studies with 3070 participants, the prevalence of newly diagnosed hypertension was 2.96% (95% confidence interval [CI], 1.15%–7.43%; I², 80%). No significant differences were observed in the subgroup analyses. Across 30 studies with 1782 individuals, the average systolic blood pressure was 109.88 mmHg (95% CI, 108–111.75; I², 92.2%), and diastolic blood pressure was 70.99 mmHg (95% CI, 68.84–73.14; I², 95.7%). In 12 studies with 339 individuals, the average mean arterial pressure was 82.01 mmHg (95% CI, 79.84–84.19; I², 93.6%). Conclusions: These findings suggest that nearly 3 in 100 healthy individuals with uncomplicated pregnancies are diagnosed with de novo essential hypertension within one year postpartum. This underscores the need to extend cardiovascular screening to all postpartum individuals for one year, regardless of medical or pregnancy history.